Influence of selected surfactants on the tackiness of acrylic polymer films - Sathaporn Nimkulrat (2018)
Anti-tacking agents are always necessary in polymeric film coating formulations in order to prevent substrate agglomeration. The objective of this study was to investigate the abilities of certain nonionic surfactants in a group of sorbitan ester in reducing the tackiness of the films obtained from aqueous acrylic polymer dispersions (Eudragit®), compared with those of talc and glyceryl monostearate (GMS). The results from the peel tests demonstrated that GMS, Span 60 and Span 40 could significantly reduce the tackiness of both Eudragit NE 30D and Eudragit RS 30D films. The mechanisms in reducing the film tackiness were investigated by analyzing the film compositions, using attenuated total internal reflectance infrared spectroscopy (ATR-IR) and optical microscopy. The storage modulus of the films was also examined. The results indicated that GMS, Span 60, and Span 40 could reduce the film tackiness by decreasing the polymer contents at the film surfaces, resulting in a notable reduction in the contact area of the polymers between the surfaces. The use of only 5% (w/w) of either GMS, Span 60 or Span 40 in the coating formulations is enough to prevent pellet agglomeration without adverse effects on film flexibility. The pellets coated with Eudragit RS 30D/RL 30D (9:1, w/w) did not exhibit any difference in the drug release profiles when either 100% (w/w) talc or 5% (w/w) GMS was used, whereas the formulations containing Span 60 or Span 40 gave a slightly faster release rate. © 2004 Elsevier B.V. All rights reserved.